Heyde Syndrome Treated by Conventional Aortic Valve Replacement - Garcia,Leonardo Rufino (2019)
Abstract Heyde syndrome manifests as aortic stenosis associated with gastrointestinal bleeding. We describe the case of a 64-year-old man who came to the emergency room due to acute heart failure and intermittent gastrointestinal bleeding. Treatment involves initial correction of anemia and heart failure followed by aortic valve replacement. The prosthesis used depends on the characteristics of each patient and valve replacement allows the resolution of bleeding in most cases. Gastrointestinal bleeding in patients with aortic stenosis is associated with severity of the valve obstruction. A mechanical prosthesis was used with no recurrent bleeding even with the need for lifelong anticoagulation therapy.